2016
DOI: 10.18553/jmcp.2016.22.7.833
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship Between Long-Term Systemic Corticosteroid Use and Related Complications in Patients with Severe Asthma

Abstract: Funding for this study was provided by GlaxoSmithKline, Study number H0-15-15930, to Analysis Group for the conduct of this study. Lefebvre, Duh, and Gozalo are employees of Analysis Group, a contract research organization that has received research grants from GlaxoSmithKline. Robitaille was employed by Analysis Group at the time of this study. Yancey, Forshag, Lin, and Albers are employees of GlaxoSmithKline and own company stock. Dalal and Ortega were employed by GlaxoSmithKline at the time of this study. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
112
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 24 publications
11
112
1
3
Order By: Relevance
“…We followed patients from the time of SCS initiation until the time they experienced an event or were otherwise censored. The use of large UK databases containing longitudinal medical record data allowed us to examine a median of almost 10 years before the first SCS prescription to exclude prior SCS use, with subsequent follow-up of a median of 7 years, much longer than prior studies in asthma with reported mean and median follow-up periods of 1–5 years 79,15,25. Moreover, earlier studies examined effects of ongoing (rather than initiating) SCS exposure7,8,2527 or ruled out previous exposure for only ≤12 months before the index prescription 9,15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed patients from the time of SCS initiation until the time they experienced an event or were otherwise censored. The use of large UK databases containing longitudinal medical record data allowed us to examine a median of almost 10 years before the first SCS prescription to exclude prior SCS use, with subsequent follow-up of a median of 7 years, much longer than prior studies in asthma with reported mean and median follow-up periods of 1–5 years 79,15,25. Moreover, earlier studies examined effects of ongoing (rather than initiating) SCS exposure7,8,2527 or ruled out previous exposure for only ≤12 months before the index prescription 9,15…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies included limited patient populations, ie, those classified as having severe asthma79,25 or those prescribed SCS for prespecified lengths of time 26,27. Studies from the USA included low-income7,8 or employed15,2528 populations, selective populations with limited or better-than-average access to care, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was driven by asthma‐associated oral corticosteroid (OCS) use. In addition, the increased risk of adverse effects is dependent on corticosteroid dosage . Dalal et al found that long‐term corticosteroid users (≥6 months) with low‐ (<5 mg/day), medium‐ (≥5‐10 mg/day), and high‐dosage (>10 mg/day) exposure had, respectively, a 2.5‐, 2.95‐, and 3.32‐fold greater adjusted relative risk of developing any steroid‐related complication compared with steroid nonusers.…”
Section: Introductionmentioning
confidence: 99%
“…These patients, although fortunately infrequent, consume the largest health care resources for asthma care [7]. They often have significant adverse effects from their doses of corticosteroids [8] and these are the patients who may benefit most with the advent of biologics that target the Th2 cytokine pathways [9]. …”
Section: Introductionmentioning
confidence: 99%